Stylistic difficulties of translating political literature - Saidova Dildora Farhod qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Practically, stylistic devices in almost all languages are similar still though their functions in speech vary. Identical stylistic devices are used differently in languages; they perform different functions and have different value in stylistic system of their language what actually explains their necessity when transformations in translation occur. The stylistic changes are as necessary as grammatical or lexical ones. A translator should not try to preserve the stylistic device given in the sentence, but reproduce its function in the target language.